1890 Okla. Stat. 476, ch. 25, art. 38,§§ 20. - (:unkn) unknown (My University, 1890)
Every person who carries concealed about his person and [sic]§description of firearms, being loaded or partly loaded, or any sharp or dangerous weapon, such as is usually employed in attack or defense of the person, is guilty of a misdemeanor.
Keywords: CARRY - CONCEALED